Draft Tenth Plan 2002-2007 and Draft Annual Plan 2002-2003 Part-III Government of Tripura - Planning Commission (Planning Commission, 2002)
Coincidence of the sixth five-year plan, 1980—85 with the opening of a new decade presents an opportunity for reviewing the achievements of the past three decades of planned development in this state and also for assessing the problems and promises of future development. 2. With 174 thousand sq. Kms. Area and 56.4 million as its population (according to the 1971 census), Bihar is the seventh largest state in the Indian union in terms of area and second largest in terms of population. Although Bihar has only 5.3 per cent of the area of the country, 10.3 per cent of the total population of the country live within the state.
Planning (P&C) Department